The permafrost environment of northwest Hurd Peninsula (Livingston Island, maritime Antarctic): preliminary results - Vieira, Gonçalo (2019)
The permafrost spatial distribution in Hurd Peninsula (Livingston Island, Antarctic) and its thermal state are the focus of the ongoing research. A multidisciplinary approach that includes meteorological and ground temperature monitoring, geomorphological mapping and geophysical surveying has been used. The results from this research indicate that ice-cored moraines and active rockglaciers are present down to sea-level. Permafrost in bedrock is more difficult to assess. It is present at 275m ASL in Reina Sofia Hill, with an active layer ca. 1m deep. At 100m the Electrical Tomography Resistivity data suggests that permafrost is present, at least under snow patches. At 35m ASL in bedrock permafrost hasn’t been found. However, more research is needed for assessing the spatial distribution of permafrost. Drilling and borehole temperature monitoring are the main objectives of the next Antarctic campaigns.